Penerapan Metode Dempster Shafer Untuk Sistem Deteksi Gangguan Kecemasan Obsessive Compulsive Disorder Berbasis Web - Saragih, Nidia Enjelita; Adawiyah, Robiatul (STMIK Budi Darma, 2021)
Obsessive Compulsive disorder or OCD is a type of anxiety disorder that makes someone wasting so much time in doing the same things reccurently. it cause distress and significant impairment. This anxiety disorder will becoming worse if someone didn't realize and get psychologist help. An expert system that diagnose OCD would be the initial step of detection, so this disorder can be handled sooner. By implementing Dempster Shafer method, this expert system produce percentage value of someone having this disorder, based on the inputted symptons. If the result more than 60%, the user need a psychologist's treatment before it coming worse. The system is web based, so it is handy to access.